Chemical constituents of hedyotis pinifolia wall. Collected in Thua Thien Hue - Khieu Thi Tam; Nguyen Thi Hoang Anh; Nguyen Van Tuan; Dao Duc Thien; Tran Duc Quan; Nguyen Thanh Tam; Nguyen Chi Bao; Trinh Thi Thuy; Tran Van Sung (Vietnam Journal of Science and Technology, 2018)
This study reports the chemical constituents from the whole plants Hedyotis pinifolia Wall. Ex G. Don (now accepted as Oldenlandia  pinifolia (Wall. Ex G. Don) Kuntze) collected  in Thua Thien Hue province. Thirteen compounds were isolated by chromatography method. Their structures were elucidated using MS and NMR analysis and compared with reported data. They contain three anthraquinones, a carotenoid, two triterpenes, four iridoid glucosides and three flavonoid glycosides. Four of them were found for the first time in this genus.